Analysis of Reading Readiness in Indonesian Subject Students with Spelling Method Grade 3 SDN 237 Kopo Elok - Muhammad Iqbal Firdaus; Yuli Tri Wiyanto; lysda Reviyanti (Journal of Social Science)
This research has the objective of knowing reading readiness for Indonesian students in the spelling method for class 3 of SD Negeri 237 Kopo Elok and what factors are inhibiting and supporting factors in reading readiness in Indonesian students with spelling. method for class 3 SD Negeri 237 Kopo Elok. The type of research used is direct research where in this research the researcher goes directly to the field to get information and data. Even though the research method used by the researcher is a descriptive qualitative method, the research is carried out by looking at the situation in order to obtain information and data according to the situation that occurs. The method of combining data uses the triangulation method, namely observation, interviews and documentation. that the results of interviews and observations that have been conducted by researchers on a number of respondents regarding the analysis of students' reading readiness for Indonesian subjects with the spelling method for grade 3 SD Negeri 237 Kopo Elok and the inhibiting and supporting factors for readingreadiness, including the following: Nf : not yet knows consonants, can't read syllables, lacks confidence and likes to daydream during lessons, lazy Ni : has a passion for learning, is happy when the teacher orders her to read and can already distinguish sounds from letters. Whereas Aq : already knows consonants, already knows syllables, already knows how to hold a book when reading properly and is never latefor school. that students' reading readiness is good enough even though there are some students who still experience problems in reading readiness, namely laziness, lack of experience in reading, not yet recognizing consonants, simple sentences, lack of my love and attention from their parents as well as lack of student motivation in reading readiness.